Magnitude of Deaths due to Organophosphorus Compounds Poisoning in Bangladesh-A Study at Dhaka Medical College (Community Based Medical Journal, 2014)
Poisoning with Organophosphorus compounds (OPC) is one of the important leading causes of morbidity and mortality for the countrymen of Bangladesh. OPC poisoning is a common cause of acute poisoning. The study was conducted to evaluate the magnitude of death due to OPC poisoning. This paper presents the study of total 852 cases of poisoning comprising 6.42% of the total 13,300 autopsies done during the period of three years (from 01/01/2009 to 31/12/2011) at Dhaka Medical College Mortuary. Of them, there were 478 cases of OPC poisoning. Most of the victims were from rural areas i.e. 296 cases (61.92%) and 182 cases (38.07%) from urban areas. 274 male victims (57.32%) outnumbered females i.e. 204 cases (42.67%) and the most affected age group was 21-30 years i.e. 214 cases (44.76% ). Farmers were the commonest victim i.e. 270 cases (56.48%) followed by housewives i.e. 105 cases (21.96%). Ingestion was the commonest route of poisoning i.e. 460 cases comprising 96.23% followed by 12 cases of inhalation (2.51%) and others. Suicide dominated the list of manner of death i.e. 466 cases comprising 97.48% followed by accidental i.e. 12 cases (2.51%) of the total 478 cases of OPC poisoning.CBMJ 2014 July: Vol. 03 No. 02 P: 29-33